Review of production responses from cows fed calcium salt of isobutyric and mixed 5-carbon volatile fatty acids - Dunham, James R. (Kansas Agricultural Experiment Station, 2012)
Recent developments in dairy cattle nutrition have resulted in the marketing of a calcium salt of isobutyric and mixed 5-carbon volatile fatty acids (IsoPlus®). The FDA approved product has been neutralized with calcium to form a dry salt of the acids, which are found naturally in the rumen. The following review of research results is intended as a guide for feeding IsoPlus®).
Keywords: Dairy; Calcium salt; Isobutyric; Volatile fatty acid; Nutrition